The Effect of Marketing Mix on Satisfaction and Its Implications on Visitor Loyalty (A Survey on Visitors in Alamendah Tourism Village, Rancabali District, Bandung Regency) - Holipudin, Apid; Suryaman, Suryaman; Febrian, Feby (Greenation Research & Yayasan Global Resarch National, 2024)
The purpose of this study is to find out and analyze: Marketing Mix on Satisfaction and its implications on Visitor Loyalty a visitor survey in Alamendah Tourism Village, Rancabali District, Bandung Regency, both simultaneously and partially.The research methods used in this study are descriptive and verifiative methods, the unit of analysis in this study is the visitors in Tourism Village A; Amendqah Rancabali District, Bandung Regency with a sample of 30 people. And the analysis methods used are quantitative analysis and path analysis. Based on the results of the study, it was found that the marketing mix on satisfaction and its implications on visitor loyalty visitor surveys in Alamendah Tourism Village, Bandung Regency in general can be said to be good, the marketing mix in Alamendah Tourism Village, Bandung Regency is currently considered good. The marketing mix simultaneously affects visitor satisfaction in Alamendah Tourism Village, Bandung Regency. However, partial visitor satisfaction predominantly affects customer loyalty.Because satisfaction predominantly affects visitor loyalty, being the first priority in improving the marketing mix in Alamendah Tourism Village, Bandung Regency is expected to consistently maintain existing conditions, thereby increasing the quality of comprehensive visits/tourists.